Information Asymmetry Moderates the Impact of Green Intellectual Capital and Real Earnings Management on Future Stock Returns - Murwaningsari, Etty; Sistya Rachmawati; Mazzlida Mat Deli (Journal of Applied Business and Technology, 2025)
The aim of this study is to (1) analyze the impact of green intellectual capital and real earnings management on future stock returns. (2) The role of information asymmetry as a moderating variable for the impact of green intellectual capital and real profit management on future stock returns. This research method uses secondary data from companies in the non-cyclical consumer sector listed on the Indonesian Stock Exchange (BEI). The research sample was selected in the period 2021-2022 based on purposive sampling criteria–, resulting in 158 observations. The data analysis was performed using the moderated regression analysis (MRA) approach to test the relationship between the variables in this study. The results of this investigation show that: (1) Green intellectual capital and real earnings management have a positive impact on future stock returns. (2) Information asymmetry does not weaken the relationship between green intellectual capital and future stock returns, so that it is classified as a moderating predictor. On the other hand, information asymmetry is shown to attenuate the impact of real earnings management on future stock returns, indicating that this variable acts as a full moderator. (3) The control variable leverage has no effect on future stock returns, while firm size has a negative effect on future stock returns.